Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1209/epl/i2003-10194-y
|View full text |Cite
|
Sign up to set email alerts
|

The non-dissipative damping of the Rabi oscillations as a “which-path” information

Abstract: Rabi oscillations may be viewed as an interference phenomenon due to a coherent superposition of different quantum paths, like in the Young's two-slit experiment. The inclusion of the atomic external variables causes a non dissipative damping of the Rabi oscillations. More generally, the atomic translational dynamics induces damping in the correlation functions which describe non classical behaviors of the field and internal atomic variables, leading to the separability of these two subsystems. We discuss on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 23 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…The damping factor shown by this last approximated expression, which is at the origin of the non dissipative damping of the Rabi oscillations [7,22,23], is due to the increasing distance in the phase space [24] of the two deflected components of the translational wave packet [25]. Similar behaviors hold for the other coefficients of eq.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The damping factor shown by this last approximated expression, which is at the origin of the non dissipative damping of the Rabi oscillations [7,22,23], is due to the increasing distance in the phase space [24] of the two deflected components of the translational wave packet [25]. Similar behaviors hold for the other coefficients of eq.…”
mentioning
confidence: 55%
“…The visibility V of the interference pattern and the distinguishability D of the quantum paths can in some extent coexist, and as shown by Englert in its quantitative analysis of complementarity [5,6], they satisfy the inequality D 2 + V 2 ≤ 1. According to this analysis and in the ambit of the optical Stern-Gerlach (SG) model, we have recently shown [7] that the visibility of the Rabi oscillations and the distinguishability of the two atomic translational paths satisfy the equality relation D 2 +V 2 = 1 when pure initial states are considered.When applied to a composite system, the superposition principle leads to quantum correlations (entanglement), which may hide the individuality of the subsystems. Differently from the classical case, and in idealized configurations, two quantum systems that have interacted for a time, generally do not recover their individuality, even if the subsystems become spatially separated.…”
mentioning
confidence: 98%
“…It has already been shown that this non dissipative coupling leads to a decoherence in the dynamics of a single atom [11,12,13] and also affects the entanglement in the internal dynamics of two atoms that successively interact with the same cavity [14]. As will shown in what follows, the same interaction gives rise to a disentanglement of the bipartite system which exhibits strong analogies with the disentanglement generated by the vacuum noise [4,8].…”
Section: Introductionmentioning
confidence: 68%
“…As a consequence, the density operator |ψ(t) ψ(t)| must be traced on the cavity fields and on the atomic translation variables. Taking into account the normalization of kets (12) and (13), and using relation (9) we obtain ρ AB (t) = T r transl,f ield (|ψ(t) ψ(t)|)…”
Section: A Two Atomsmentioning
confidence: 99%
See 1 more Smart Citation